PERAN PANGAN POKOK LOKAL TRADISIONAL DALAM DIVERSIFIKASI KONSUMSI PANGAN - Hanafie, Rita (Jurnal Sosial Ekonomi Pertanian, 2010)
Food consumption diversification aim to lessen the storey level consume the fundamental food of rice, replace it with traditional local fundamental food and improve the score quality of food consumption. Research aim to know the storey level consume the food, score quality of food consumption and role of traditional local fundamental food in pattern food consumption of the household. Research done in Sub district of Kauman Tulungagung Regency. Analysis unit is household at villages. Analysis consume the food and scor PPH done to know the storey, level consume the food and score quality of food consumption. Role of traditional local fundamental food consumption analysed discriptifly qualitative. Research result indicate that the consumption of energy is 60,47 % AKE with score quality of food consumption is 39,39. Though tubers have ever been effective enough consumed however rice still occupy the important position in fundamental food consumption. The position of traditional local fundamental food in pattern food consumption still is snack.Keywords: traditional local fundamental food, food consumption diversification